An elderly patient with a rare blood group in Bangladesh: a case report (BIRDEM Medical Journal, 2025)
The Bombay Blood Group is a rare blood type characterized by the absence or deficiency of the H antigen. It was first identified in Mumbai (formerly Bombay) in 1952, thus it was named as. This blood group lacks the A, B, and H antigens on red blood cells, and its serum contains anti-A, anti-B, and anti-H antibodies. A 60-year-old male was admitted to BIRDEM General Hospital with uncontrolled diabetes mellitus, hypertension, right-sided pneumonia, chronic kidney disease and severe anemia. Due to his critically low hemoglobin level of 6.5 gm/dl, he required two units of packed red cells. During pre-transfusion testing, a blood sample was taken and sent to our Transfusion Medicine Department. At the time of blood grouping we surprisingly noticed that he has ‘Bombay Blood Group’. It is a very rare type of blood group and on routine blood grouping behaves as “O” unless reverse grouping or serum grouping has been done but can receive transfusion from only peoples having Bombay group. Interestingly, individuals with the Bombay phenotype are likely to have family members with the same blood group. His three sons and one daughter were tested for blood grouping, all showed “O” positive with Rhesus “D” positive. Despite no known family members or records in our blood bank having the Bombay blood group, his sons embarked on a search for Bombay phenotype donors for his transfusion. They succeeded in locating two donors with the Bombay blood group, one from Narayanganj and another from Chandpur. Following treatment for infection and diabetes control, he received two units of Bombay red cell concentrate transfusion. After receiving blood transfusion, his clinical condition improved.BIRDEM Med J 2025; 15(1): 44-46